Rock climbing-related injuries: A clinical and imaging overview - Miro, P.; Miro, E.; Ho, T.; Feuerborn, M.; Crawford, A.; Schöffl, V. (Current Sports Medicine Reports, 2024)
The rise in popularity of competitive and recreational rock climbing, particularly following its inclusion in the 2021 Summer Olympics, has led to a corresponding increase in rock climbing-related injuries. Due to the sport's unique biomechanical demands, it often presents injuries not commonly seen in other sports. Additionally, although some injuries align with those encountered in other sports, they manifest through distinctive climbing-related mechanisms unfamiliar to many clinicians. This paper delves into 10 prevalent injuries associated with the sport, exploring both sport-specific injuries and the unique mechanisms behind commonly encountered ones. Each injury receives a comprehensive overview, detailing its clinical presentation, evaluation, specific injury mechanisms with photographic and graphic illustrations, imaging representations, and treatment considerations. This paper aims to serve as a valuable reference for clinicians dealing with rock climbing-related injuries in clinical practice.